2021
DOI: 10.1101/2021.05.19.444882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Structure of ChAdOx1/AZD-1222 Reveals Interactions with CAR and PF4 with Implications for Vaccine-induced Immune Thrombotic Thrombocytopenia

Abstract: Adenovirus derived vectors, based on chimpanzee adenovirus Y25 (ChAdOx1) and human adenovirus type 26 are proving critical in combating the 2019 SARS-CoV-2 pandemic. Following emergency use authorization, scale up in vaccine administration has inevitably revealed vaccine related adverse effects; too rare to observe even in large Phase-III clinical trials. These include vaccine-induced thrombotic thrombocytopenia (VITT), an ultra-rare adverse event in which patients develop life-threatening blood clots 5-24 day… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…While we con rmed the previously observed interaction of PF4 with ChAdOx1 nCoV-19, PF4 did not form distinct complexes with Ad26.COV2.S or puri ed ChAdOx1 nCoV-19 virion preparations, highlighting the role of impurities in ChAdOx1 nCoV-19 for the observed interactions 6 . Consistent with our ndings in DLS, a recent study using cryo-electron microscopy of ChAdOx1 nCoV-19 established a possible electrostatic interaction of the positively charged PF4 and the negatively charged adenoviral hexon polypeptide 10 as a likely functional basis for the interactions. We now show that this interaction can be e ciently abrogated by purifying the intact adenoviral vector from the vaccine formulation.…”
Section: Discussionsupporting
confidence: 91%
“…While we con rmed the previously observed interaction of PF4 with ChAdOx1 nCoV-19, PF4 did not form distinct complexes with Ad26.COV2.S or puri ed ChAdOx1 nCoV-19 virion preparations, highlighting the role of impurities in ChAdOx1 nCoV-19 for the observed interactions 6 . Consistent with our ndings in DLS, a recent study using cryo-electron microscopy of ChAdOx1 nCoV-19 established a possible electrostatic interaction of the positively charged PF4 and the negatively charged adenoviral hexon polypeptide 10 as a likely functional basis for the interactions. We now show that this interaction can be e ciently abrogated by purifying the intact adenoviral vector from the vaccine formulation.…”
Section: Discussionsupporting
confidence: 91%
“…As far as we know, the differences between the vaccines are as follows: 1) The type of adenovirus is different (human Ad26 and chimpanzee adenovirus in the AD26 and ChA vaccines, respectively); 2) the human cell lines by which adenovirus are produced are different: T-REx-293 cells for ChA and PER.C6 TetR cells for AD26 [ 44 ]; 3) ChA contains a large number of host cell proteins differently from AD26 [ 10 , 44 , 45 ]; 4) chimpanzee adenovirus has a stronger negative charge than human AD26 [ 40 ]. Molecular simulations suggest that the chimpanzee adenovirus charge, combined with aspects of the virus shape, could allow it to bind to the positively charged PF4 protein [ 46 ]; 5) The number of viral particle in the AD26 vaccine is 3.3-fold higher than that in the ChA vaccine [ 47 , 48 ], possibly implying a higher spike protein and adenoviral protein burden. 6) EDTA is present in the ChA vaccine but not in the AD26 vaccine [ 47 , 48 ], and it has been hypothesized that it favors the development of inflammation at the vaccine inoculation site.…”
Section: Discussionmentioning
confidence: 99%
“…This PF4-dependent thrombotic disorder is now referred to as vaccine-induced immune thrombotic thrombocytopenia (VIIT) and is characterized by thrombosis in unusual regions of cerebral sinuous veins and lung or splanchnic veins with mild-to-severe thrombocytopenia. Structural studies of ChAdOx1 suggested that the electronegative potential of the viral capsid could lead to interaction with PF4, leading to complex formations and antibody production, as observed in HIIT [152]. The probability to develop VIIT has been calculated to be one per 250,000 vaccinees.…”
Section: Adverse Effects Associated With Adenovirus-based Vaccinesmentioning
confidence: 99%